Negative pole piece, preparation method thereof and solid-state battery

By drilling holes in the skeleton layer of the negative electrode plate and forming a three-layer filler structure, the problem of increased battery stress caused by the volume expansion of the silicon-based negative electrode material is solved, and the effect of reducing the expansion of the electrode piece and improving the battery cycle life is achieved.

CN119340343APending Publication Date: 2025-01-21FARASIS TECH (GANZHOU) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411243033.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The volume expansion of the silicon-based anode material in lithium-ion batteries during charging and discharging causes an increase in the internal stress of the battery, which may lead to battery damage or capacity reduction, increasing safety risks.

Method used

By drilling holes in the skeleton layer of the negative electrode sheet, a skeleton structure is established to provide space for storing silicon, suppress silicon expansion, and form a stable conductive network through the three-layer structure of the first filler and the second filler.

Benefits of technology

Reduce the expansion of the polar sheet, increase the cycle life of the battery, and reduce the possibility of battery damage and safety risk.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340343A_ABST
    Figure CN119340343A_ABST
Patent Text Reader

Abstract

The invention provides a negative pole piece and a preparation method thereof, and a solid-state battery, and the negative pole piece comprises a pole piece skeleton layer which comprises a plurality of skeleton holes; the framework holes are filled with the first filler; the second filler is filled with the second filler; the first filler comprises the following components: a silicon carbon material, a conductive agent, a sodium carboxymethyl cellulose glue solution, a first binder, a second binder and a solid electrolyte. The preparation method has the beneficial effects that the framework layer of the pole piece is perforated to establish a framework structure, so that a space for storing silicon is provided, the expansion of silicon is inhibited, the contact loss of silicon expansion electrons is prevented, a stable conductive network is provided, the expansion of the pole piece is reduced, and the cycle life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy, and in particular to a negative electrode plate and a preparation method thereof, and a solid-state battery. Background Art

[0002] With the demand for high capacity and long battery life of lithium-ion batteries in new energy vehicles, communications and portable devices, the development of lithium-ion batteries has reached a bottleneck. Currently, the widely used negative electrode materials are various carbon materials based on graphite, with a theoretical capacity of only 372mAh / g. In actual application, it is close to the theoretical capacity and it is difficult to meet higher capacity requirements.

[0003] Among the many high-capacity negative electrode materials currently available, silicon-based negative electrode materials have attracted extensive attention and research due to their high specific capacity (4200mAh / g), abundant resource reserves, and low price. They are the most mature and commercially advanced high-capacity negative electrode materials in production and application technology, and are also strong competitors for the next generation of high-energy-density lithium-ion battery negative electrode materials. However, silicon has a large volume expansion: the formation of Li 22 When Si5 (specific capacity 4200mAh / g), the volume expansion can reach 400%, forming Li 15 When Si4 (specific capacity 3580mAh / g) is used, the volume expansion can reach 300%, which will increase the stress inside the battery due to the volume expansion, which may cause battery damage or capacity reduction. In addition, the expansion may also cause deformation or rupture of the battery shell, thereby increasing the safety risk of the battery. Summary of the invention

[0004] The main purpose of the present invention is to provide a negative electrode plate and a preparation method thereof, and a solid-state battery, aiming to solve the problem of increased stress inside the battery caused by volume expansion.

[0005] The present invention provides a negative electrode sheet, comprising:

[0006] A pole piece skeleton layer, wherein the pole piece skeleton layer comprises a plurality of skeleton holes;

[0007] A first filler, wherein the first filler is filled in the pores of the framework;

[0008] The first filler comprises silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue and binder.

[0009] Furthermore, the binder includes a first binder and a second binder, and the components of the first filler include, by mass percentage:

[0010] Silicon carbon material 70%~90%;

[0011] Conductive agent 0.5% to 2%;

[0012] Sodium carboxymethyl cellulose 0.5-2%;

[0013] The first binder 1-3%;

[0014] The second binder 1-5%;

[0015] Solid electrolyte 0~27%.

[0016] Furthermore, it also includes a second filler, wherein the components of the second filler include a polymer solid electrolyte and a lithium salt;

[0017] The second filler is filled in the skeleton pores and forms a three-layer structure of first filler-second filler-first filler with the first filler.

[0018] Furthermore, the components of the second filler, measured by mass percentage, include:

[0019] Polymer solid electrolyte 90%~99%;

[0020] Lithium salt 1-10%.

[0021] Furthermore, the polymer solid electrolyte is at least one selected from polyethylene oxide, polyacrylonitrile, and polymethyl methacrylate.

[0022] Furthermore, the total height or volume of the skeleton pores is set to 1, the filling amount height or volume of the first layer accounts for 1 / 3 to 1 / 4, the filling amount height or volume of the second layer accounts for 1 / 3 to 1 / 2, and the filling amount height or volume of the third layer accounts for 1 / 3 to 1 / 4. Optionally, the height or volume of the first layer accounts for 1 / 3, the height or volume of the second layer accounts for 1 / 3, and the height or volume of the third layer accounts for 1 / 3.

[0023] Furthermore, the solid electrolyte is at least one selected from lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide lithium phosphorus sulfur, lithium phosphorus sulfur chlorine, and lithium germanium phosphorus sulfur.

[0024] Furthermore, the diameter of the skeleton pores is 1 to 100 mm.

[0025] Furthermore, the spacing between the skeleton holes is 1 to 100 mm.

[0026] Furthermore, when the depth of the skeleton pores is set to H, the distance between the skeleton pores is set to L, and the thickness of the negative electrode sheet is set to T, the following formula H≤T, L / T≥10 is satisfied.

[0027] Furthermore, the skeleton holes are evenly distributed in the horizontal and vertical directions at preset intervals.

[0028] Furthermore, the pole piece skeleton layer includes a graphite layer and a copper foil layer, and the skeleton holes are arranged on the graphite layer.

[0029] Furthermore, the sum of the volumes of the skeleton pores occupies 10%-90% of the total volume of the pole piece skeleton layer.

[0030] Furthermore, the pole piece skeleton layer is composed of one of graphite, hard carbon and soft carbon.

[0031] The present invention also provides a method for preparing a negative electrode sheet, comprising:

[0032] Mixing graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder and a solid electrolyte to obtain a first slurry;

[0033] Applying the obtained first slurry to a carrier to form a uniform coating, and drying and rolling to obtain a current collector;

[0034] Punching the current collector to obtain a pole piece skeleton layer;

[0035] Filling the pores of the pole piece skeleton layer with filler slurry and drying to obtain a negative pole piece, wherein the filler comprises at least silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, a first binder, a second binder and a solid electrolyte.

[0036] Furthermore, the filler includes a first filler and a second filler, and the step of filling the filler slurry into the pores of the pole piece skeleton layer and drying to obtain the negative pole piece includes:

[0037] Filling the skeleton pores with the second slurry corresponding to the first filler, and controlling the filling height or volume to be 1 / 4 to 1 / 3 of the total height or volume of the skeleton pores, and then drying;

[0038] The third slurry corresponding to the second filler continues to fill the skeleton pores, and the filling height or volume is controlled to be 1 / 3 to 1 / 2 of the total height or volume of the skeleton pores, and then dried;

[0039] The second slurry corresponding to the first filler continues to fill the skeleton pores, and the filling height or volume is controlled to be 1 / 4 to 1 / 3 of the total height or volume of the skeleton pores, and then dried to obtain the negative electrode sheet.

[0040] The present invention also provides a solid-state battery, comprising the negative electrode sheet described in any one of the above items, or a negative electrode sheet prepared by the method for preparing the negative electrode sheet described in any one of the above items.

[0041] The beneficial effects of the present invention are as follows: by punching holes in the pole piece skeleton layer, a skeleton structure is established, thereby providing space for storing silicon, inhibiting the expansion of silicon and preventing electronic contact loss caused by silicon expansion, providing a stable conductive network, thereby reducing pole piece expansion and improving battery cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic diagram of a partial cross-sectional structure of a negative electrode sheet according to an embodiment of the present invention;

[0043] Figure 2 The present invention is a schematic diagram of a method for preparing a negative electrode sheet according to an embodiment of the present invention.

[0044] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly. The connection can be a direct connection or an indirect connection.

[0047] The term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there may be three relationships. For example, A and B can represent three situations: A exists alone, A and B exist at the same time, and B exists alone.

[0048] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0049] Reference Figure 1The present invention provides a negative electrode sheet, comprising:

[0050] A pole piece skeleton layer 300, wherein the pole piece skeleton layer 300 includes a plurality of skeleton holes;

[0051] A first filler 100, wherein the first filler 100 is filled in the skeleton pores;

[0052] The first filler 100 includes silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue and binder.

[0053] In this embodiment, punching can be performed by punching, drilling, photolithography or laser to construct a rigid skeleton. Specifically, by providing a rigid support and expansion space for silicon expansion constraints, the Li 22 Si5 or Li 15 When Si4 is used, expansion space is provided, thereby increasing the stress inside the battery, thereby reducing the possibility of battery damage or capacity reduction, and reducing the safety risk of the battery. The skeleton holes can be evenly distributed in the horizontal and vertical directions, the spacing between two adjacent skeleton holes is 1mm-100mm, and the diameter of the holes is 1mm-100mm, so that the pole piece skeleton layer has sufficient stability while ensuring the provision of expansion space.

[0054] In one embodiment, the pole piece skeleton layer has the functions of deintercalating and extracting lithium and conducting electrons, and is a negative electrode active material, which can be graphite, hard carbon, soft carbon, etc., preferably graphite.

[0055] In one embodiment, the skeleton hole does not penetrate the pole piece skeleton layer, the pole piece skeleton layer includes a graphite layer and a copper foil layer, and the skeleton hole only penetrates the graphite layer. Figure 1 Only the structure of the graphite layer is shown.

[0056] In one embodiment, the sum of the volumes of the skeleton pores occupies 10%-90% of the total volume of the pole piece skeleton layer.

[0057] Specifically, the binder includes a first binder and a second binder, and the components of the first filler include, by mass percentage:

[0058] Silicon carbon material 70%~90%;

[0059] Conductive agent 0.5% to 2%;

[0060] Sodium carboxymethyl cellulose 0.5-2%;

[0061] The first binder 1-3%;

[0062] The second binder 1-5%;

[0063] Solid electrolyte 0~27%.

[0064] Among them, CMC (Carboxymethyl Cellulose) is carboxymethyl cellulose, and the sodium carboxymethyl cellulose glue is formed by putting sodium carboxymethyl cellulose into deionized water and dispersing it evenly. The first binder is SBR (Styrene-Butadiene Rubber), polyvinyl alcohol (PVA), conductive polymer polyaniline (PANI), polyacrylonitrile (PAN), etc., and the second binder is PAA (Polyacrylic Acid), polyamideimide (PAI), polyimide (PI), etc. The solid electrolyte is a commonly used electrolyte in the industry, which is at least one selected from lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide lithium phosphorus sulfur, lithium phosphorus sulfur chlorine, and lithium germanium phosphorus sulfur.

[0065] In one embodiment, a second filler 200 is further included, wherein the second filler 200 includes a polymer solid electrolyte and a lithium salt;

[0066] In one embodiment, the diameter of the skeleton pores is 1 to 100 mm.

[0067] In one embodiment, the spacing between the skeleton holes is 1 to 100 mm.

[0068] In one embodiment, when the depth of the skeleton pores is set to H, the distance between the skeleton pores is set to L, and the thickness of the negative electrode sheet is set to T, the following formula H≤T, L / T≥10 is satisfied.

[0069] In one embodiment, the skeleton holes are evenly distributed at preset intervals in the horizontal and vertical directions.

[0070] The second filler 200 is filled in the skeleton hole and is formed with the first filler 100. The three-layer structure of the first filler 100-the second filler 200-the first filler 100 is arranged in the direction from close to the copper foil to far away from the copper foil, that is, a three-layer structure of a silicon carbon layer-a polymer flexible layer-a silicon carbon layer can be formed in the skeleton hole. Such a three-layer structure can improve the capacity of the negative electrode plate. The polymer flexible layer provides expansion and contraction space, maintains close contact between layers and high-speed lithium ion conduction, and the graphite rigid skeleton (i.e., the pole piece skeleton layer) provides stable support and a continuous electronic conduction network to prevent electronic contact loss after silicon expansion, affect the capacity of the battery, and improve the rate performance and cycle performance of the battery.

[0071] Specifically, the components of the second filler 200, measured by mass percentage, include:

[0072] Polymer solid electrolyte 90%~99%;

[0073] Lithium salt 1-10%.

[0074] Specifically, the polymer solid electrolyte is at least one selected from polyethylene oxide, polyacrylonitrile, and polymethyl methacrylate.

[0075] Specifically, the total height or volume of the skeleton pores is set as 1, the filling height or volume of the first layer accounts for 1 / 3 to 1 / 4, the filling height or volume of the second layer accounts for 1 / 3 to 1 / 2, and the filling height or volume of the third layer accounts for 1 / 3 to 1 / 4.

[0076] In a preferred embodiment, the height or volume fraction occupied by the first layer is 1 / 3, the height or volume fraction occupied by the second layer is 1 / 3, and the height or volume fraction occupied by the third layer is 1 / 3.

[0077] Specifically, the solid electrolyte is at least one selected from lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide lithium phosphorus sulfur, lithium phosphorus sulfur chlorine, and lithium germanium phosphorus sulfur.

[0078] Reference Figure 2 The present invention also provides a method for preparing a negative electrode sheet, comprising:

[0079] S1: mixing graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder and a solid electrolyte to obtain a first slurry;

[0080] S2: applying the obtained first slurry to a carrier to form a uniform coating, and drying and rolling to obtain a current collector;

[0081] S3: punching the current collector to obtain a pole piece skeleton layer 300;

[0082] S4: Filling the pores of the electrode skeleton layer 300 with filler slurry, and drying to obtain a negative electrode, wherein the filler comprises at least silicon-carbon material, a conductive agent, sodium carboxymethyl cellulose glue, a first binder, a second binder and a solid electrolyte.

[0083] The preparation method of sodium carboxymethyl cellulose glue is to put sodium carboxymethyl cellulose into deionized water and disperse it evenly to form sodium carboxymethyl cellulose glue. The carrier can be a foil material, and the foil material is preferably an extremely thin metal sheet, which mainly has a conductive function, a thickness of 4 to 8 um, and does not have various pores.

[0084] In one embodiment, the filler includes a first filler 100 and a second filler 200, and the step S5 of filling the filler slurry into the pores of the electrode skeleton layer 300 and drying to obtain the negative electrode comprises:

[0085] S501: Fill the skeleton pores with the second slurry corresponding to the first filler 100, and control the filling height or volume to be 1 / 4 to 1 / 3 of the total height or volume of the skeleton pores, and then dry;

[0086] S502: Continue to fill the skeleton pores with the third slurry corresponding to the second filler 200, and control the filling height or volume to be 1 / 3 to 1 / 2 of the total height or volume of the skeleton pores, and then dry;

[0087] S503: Continue to fill the skeleton pores with the second slurry corresponding to the first filler 100, and control the filling height or volume to be 1 / 4 to 1 / 3 of the total height or volume of the skeleton pores, and then dry to obtain the negative electrode sheet.

[0088] Among them, the silicon-carbon material, the conductive agent, the sodium carboxymethyl cellulose glue, the binder and the solid electrolyte are configured into a second slurry according to a certain ratio. The polymer solid electrolyte and the lithium salt are configured into a third slurry according to a certain ratio. The specific ratio configuration is described in detail above and will not be repeated here.

[0089] The present invention also provides a solid-state battery, comprising the negative electrode sheet described in any one of the above items, or a negative electrode sheet prepared by the method for preparing the negative electrode sheet described in any one of the above items.

[0090] Specifically, the positive electrode sheet of the solid-state battery is prepared by mixing the ternary material, the binder PVDF, the conductive agent, and the solid electrolyte in a certain proportion to form the positive electrode sheet.

[0091] The solid electrolyte is prepared by making a solid electrolyte sheet with a sulfide electrolyte and a binder in a certain proportion. The positive electrode sheet is composed of a mixture of the following components in mass percentage, the sum of the mass percentages of the following components is 100%, ternary 70% to 90%, binder PVDF 0.5% to 3%, conductive agent 0.5% to 5%, solid electrolyte 8 to 28%; the solid electrolyte component is composed of a mixture of the following components in mass percentage, the sum of the mass percentages of the following components is 100%, sulfide electrolyte 95% to 99.8%, binder 0.2% to 5%. The ternary is specifically NCM (Nickel-Cobalt-Manganese), and the conductive agent is (superior-grade graphite).

[0092] The following are some comparative examples and embodiments of the present application, in which the conductive agent SP is conductive carbon black (Super-P), the solid electrolyte LPSCl is lithium phosphorus sulfur chloride, the binder PVDF is polyvinylidene fluoride, the solid electrolyte PEO is polyethylene oxide, the positive electrode ternary NCM is lithium nickel cobalt manganese (Nickel-Cobalt-Manganese, LiNiCoMnO2), the binder SBR is styrene-butadiene rubber, the binder PAA is polyacrylic acid, and the polymer solid electrolyte PVDF is polyvinylidene fluoride.

[0093] Comparative Example 1:

[0094] (1) Preparation of sodium carboxymethyl cellulose glue: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion, pre-mix at 10 rpm / 600 rpm / 10 min, and then prepare sodium carboxymethyl cellulose glue at 25 rpm / 1800 rpm / 90 min for use;

[0095] (2) preparing a silicon-carbon pole piece from a graphite and silicon-carbon mixed material, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0096] (3) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0097] (4) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0098] (5) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon electrode sheet into a battery for cycle testing.

[0099] Comparative Example 2:

[0100] (1) Use laser to punch holes in the foil, forming holes with a spacing of 2 mm and a diameter of φ2 mm, which are evenly distributed in the horizontal and vertical directions;

[0101] (2) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0102] (3) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0103] (4) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0104] (5) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0105] (6) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0106] (7) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0107] Embodiment 1:

[0108] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0109] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0110] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 2 mm, a hole diameter of φ2 mm, and uniform distribution in the horizontal and vertical directions;

[0111] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0112] (5) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0113] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0114] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0115] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0116] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0117] Embodiment 2:

[0118] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0119] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0120] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 2 mm, a hole diameter of φ2 mm, and uniform distribution in the horizontal and vertical directions;

[0121] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 4 of the hole after drying;

[0122] (5) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 2 of the hole after drying;

[0123] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 4 of the holes;

[0124] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0125] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0126] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0127] Embodiment 3:

[0128] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0129] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0130] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 2 mm, a hole diameter of φ2 mm, and uniform distribution in the horizontal and vertical directions;

[0131] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 100% of the hole after drying;

[0132] (5) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0133] (6) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0134] (7) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0135] Embodiment 4:

[0136] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0137] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0138] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 2 mm, a hole diameter of φ1 mm, and uniform distribution in the horizontal and vertical directions;

[0139] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0140] (5) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0141] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0142] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0143] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0144] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0145] Embodiment 5:

[0146] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0147] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0148] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 2 mm, a hole diameter of φ50 mm, and uniform distribution in the horizontal and vertical directions;

[0149] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0150] (5) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0151] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0152] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0153] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0154] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0155] Embodiment 6:

[0156] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0157] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0158] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 2 mm, a hole diameter of φ100 mm, and evenly distributed in the horizontal and vertical directions;

[0159] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0160] (5) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0161] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0162] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0163] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0164] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0165] Embodiment 7:

[0166] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0167] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0168] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 1 mm, a hole diameter of φ2 mm, and uniform distribution in the horizontal and vertical directions;

[0169] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0170] (5) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0171] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0172] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0173] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0174] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0175] Embodiment 8:

[0176] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0177] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0178] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 50 mm, a hole diameter of φ2 mm, and uniform distribution in the horizontal and vertical directions;

[0179] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0180] (5) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0181] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0182] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0183] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0184] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0185] Embodiment 9:

[0186] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0187] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0188] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 100 mm, a hole diameter of φ2 mm, and uniform distribution in the horizontal and vertical directions;

[0189] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0190] (5) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0191] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0192] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0193] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0194] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0195] Embodiment 10:

[0196] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0197] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0198] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 2 mm, a hole diameter of φ2 mm, and uniform distribution in the horizontal and vertical directions;

[0199] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 70:2:2:3:5:18; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0200] (5) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0201] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0202] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0203] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0204] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0205] Embodiment 11:

[0206] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0207] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0208] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 2 mm, a hole diameter of φ2 mm, and uniform distribution in the horizontal and vertical directions;

[0209] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0210] (5) Prepare a slurry of polymer solid electrolyte PEO and lithium salt LiFSI in a weight ratio of 90:10; apply it to 4 and occupy 1 / 3 of the hole after drying;

[0211] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0212] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0213] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0214] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0215] Embodiment 12:

[0216] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0217] (2) preparing a graphite pole piece by using graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder SBR, and a solid electrolyte LPSCl in a weight ratio of 86:1:1:2:10;

[0218] (3) Using laser to clean the graphite pole piece until the foil is formed, forming a hole spacing of 2 mm, a hole diameter of φ2 mm, and uniform distribution in the horizontal and vertical directions;

[0219] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0220] (5) polymer solid electrolyte PVDF: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0221] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0222] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0223] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0224] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0225] Embodiment 13:

[0226] (1) Preparation of glue solution: add 1.5% CMC by mass to deionized water solvent for mixing and dispersion. Premix at 10 rpm / 600 rpm / 10 min, then prepare glue solution at 25 rpm / 1800 rpm / 90 min for use.

[0227] (2) hard carbon, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, and solid electrolyte LPSCl are prepared into a hard carbon electrode in a weight ratio of 86:1:1:2:10;

[0228] (3) Using laser to clean the hard carbon pole piece until the foil is formed, forming a hole spacing of 2 mm, a hole diameter of φ2 mm, and uniform distribution in the horizontal and vertical directions;

[0229] (4) preparing a slurry of silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue, binder SBR, binder PAA, and solid electrolyte in a weight ratio of 84:1:1:1.5:2.5:10; applying the slurry to the laser-cleaned hole, and occupying 1 / 3 of the hole after drying;

[0230] (5) polymer solid electrolyte PEO: lithium salt LiFSI are prepared into a slurry in a weight ratio of 98:2; coated in 4, and occupy 1 / 3 of the hole after drying;

[0231] (6) Apply the slurry in step 4 to the remaining holes, and after drying, it will occupy 1 / 3 of the holes;

[0232] (7) The positive electrode sheet is prepared by using a ternary positive electrode material NCM: conductive agent SP: binder PVDF: solid electrolyte LPSCl in a weight ratio of 83:5:2:10;

[0233] (8) solid electrolyte LPSCl: binder PVDF in a weight ratio of 99:1 to prepare a solid electrolyte sheet;

[0234] (9) Assemble the positive electrode sheet, solid electrolyte sheet, and silicon-carbon material into a battery for cycle testing.

[0235] Table 1 Data parameters

[0236]

[0237] Table 2 Cycle performance

[0238]

[0239] Examples 1 to 3 show that by changing the height or volume proportion of the three layers of fillers in the skeleton pores of the electrode skeleton layer, Example 3 does not have a second layer of filler for buffering, and the electrode expansion rate increases significantly, reaching 60%, and cannot be effectively restricted; In Example 2, the height or volume proportion of the second layer of filler is too high. Although the 300-cycle performance of the battery is improved and the expansion rate of the Soc100% negative electrode sheet is reduced, the height or volume proportion of the first layer of filler is reduced, and then the content of the first filler in the skeleton pores is reduced, which reduces the content of silicon-carbon material in the skeleton pores, resulting in a low proportion of silicon-carbon material in the negative electrode sheet, which will cause the capacity of the battery to decrease, and the advantage of the high capacity of the silicon-carbon material cannot be brought into play.

[0240] From Examples 1, 4 to 6, it can be obtained that by changing the diameter of the skeleton pores, although the skeleton pores can inhibit the expansion of the silicon-carbon material, as the diameter of the skeleton pores increases, the 300-cycle performance gradually decreases, and the expansion rate shows an increasing trend. However, when the diameter of the skeleton pores is 2 mm, the 300-cycle performance of the battery is 92%, and when the diameter of the skeleton pores is 1 mm, the 300-cycle performance of the battery is 91%. When the diameter of the skeleton pores is 50 mm, the 300-cycle performance of the battery is 82%, and when the diameter of the skeleton pores is 100 mm, the 300-cycle performance of the battery is 70%, showing a trend of first increasing and then decreasing. Therefore, the diameter of the skeleton pores needs to be reasonably set, and should not be too large or too small. To ensure that the 300-cycle performance of the battery remains optimal, the diameter of the skeleton pores is preferably set to 2 mm.

[0241] From Examples 7 to 9, it can be seen that by changing the size of the pore spacing of the skeleton pores, as the pore spacing of the skeleton pores continues to increase, the number of skeleton pores per unit volume decreases, which in turn leads to a decrease in the content of the silicon-carbon material in the first filler, while the volume of the pole piece skeleton layer increases accordingly, which can effectively inhibit the expansion of the silicon-carbon material in the first filler. Although this can increase the 300-cycle performance of the battery and reduce the expansion rate of the Soc100% negative electrode, the pore spacing of the skeleton pores continues to increase, resulting in a decrease in the actual number of skeleton pores, which reduces the amount of the first filler filled, thereby reducing the overall amount of silicon-carbon material corresponding to the first filler, which will cause the battery capacity to decrease. , the advantage of high capacity of silicon-carbon material cannot be brought into play. Therefore, increasing the pore spacing of the skeleton pores can improve the 300-cycle performance of the battery and reduce the Soc100% negative electrode sheet expansion rate. However, it will also lead to a decrease in the capacity of the silicon-carbon material. It is necessary to reasonably set the pore spacing of the skeleton pores to avoid the situation where the silicon-carbon material capacity is too low or the Soc100% negative electrode sheet expansion rate is too high and the 300-cycle performance of the battery is too low. In some embodiments, if the emphasis is on the 300-cycle performance of the battery and the Soc100% negative electrode sheet expansion rate, the pore spacing of the skeleton pores can be appropriately increased; if the emphasis is on the silicon-carbon material capacity of the battery, the pore spacing of the skeleton pores can be appropriately reduced.

[0242] Compared with Example 1, due to the reduction in the mass percentage of silicon-carbon material in the first layer of filler, the 300-cycle performance of the battery is reduced, and the expansion rate of the Soc100% negative electrode sheet is increased. Therefore, reducing the content of silicon-carbon material in the first layer of filler will reduce the 300-cycle performance of the battery and increase the expansion rate of the Soc100% negative electrode sheet.

[0243] Compared with Example 1, Example 11 increases the mass percentage of lithium salt in the second filler. The 300-cycle performance of the battery of Example 11 is better than the 300-cycle performance of the battery of Example 1. However, the Soc100% negative electrode sheet expansion rate of Example 11 is worse than the Soc100% negative electrode sheet expansion rate of Example 1. Therefore, when designing the battery, it is necessary to focus on one aspect. If the focus is on reducing the expansion rate of the Soc100% negative electrode sheet, the mass percentage of lithium salt will be reduced. If the focus is on the 300-cycle performance of the battery, the mass percentage of lithium salt will be increased.

[0244] Comparing Example 12 with Example 1, Example 12 uses PVDF as the second layer filler component when preparing the negative electrode sheet, and Example 1 uses PEO as the second layer filler component when preparing the negative electrode sheet. Data show that the 300-cycle performance of the battery of Example 12 is lower than that of Example 1, and the Soc100% negative electrode sheet expansion rate is higher than that of Example 1. Therefore, the performance of using PVDF as the second layer filler component is not as good as the performance of using PEO as the second layer filler component.

[0245] Comparing Example 13 with Example 1, Example 13 uses hard carbon as the electrode skeleton layer when preparing the negative electrode sheet, and Example 1 uses graphite as the electrode skeleton layer when preparing the negative electrode sheet. Data show that the 300-cycle performance of the battery of Example 13 is lower than that of Example 1, and the Soc100% negative electrode sheet expansion rate is higher than that of Example 1. Therefore, the performance of using hard carbon as the electrode skeleton layer is not as good as the performance of using graphite as the electrode skeleton layer.

[0246] It can be seen from Table 2 that the 300-cycle performance of the batteries in Examples 1-13 is all above 70%, while the 300-cycle performance of the battery in Comparative Example 1 is 65%, and the 300-cycle performance of the battery in Comparative Example 2 is 68%. The 300-cycle performance of the batteries in Examples 1-13 is higher than that in Comparative Example 1-2, and the Soc100% negative electrode sheet expansion rate of Examples 1-13 is all below 95%, and can even reach 20%. The Soc100% negative electrode sheet expansion rate of Comparative Example 1 is 125%, and the Soc100% negative electrode sheet expansion rate of Comparative Example 2 is 100%. Compared with Comparative Example 1-2, the expansion rate of Example 1-13 is also significantly reduced. Therefore, the method of punching the electrode skeleton layer can significantly improve the cycle performance and reduce the expansion rate.

[0247] The beneficial effects of the present invention are as follows: by punching holes in the pole piece skeleton layer, a skeleton structure is established, thereby providing space for storing silicon, inhibiting the expansion of silicon and preventing electronic contact loss caused by silicon expansion, providing a stable conductive network, thereby reducing pole piece expansion and improving battery cycle life.

[0248] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of the claims of the present invention.

Claims

1. A negative electrode plate, characterized in that: include: A pole piece skeleton layer, wherein the pole piece skeleton layer comprises a plurality of skeleton holes; A first filler, wherein the first filler is filled in the pores of the framework; The first filler comprises silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue and binder.

2. The negative electrode sheet according to claim 1, characterized in that: The binder includes a first binder and a second binder, and the components of the first filler include, by mass percentage: Silicon carbon material 70%~90%; Conductive agent 0.5% to 2%; Sodium carboxymethyl cellulose 0.5-2%; The first binder 1-3%; The second binder 1-5%; Solid electrolyte 0~27%.

3. The negative electrode sheet according to claim 1, characterized in that: Also included is a second filler, the second filler comprising a polymer solid electrolyte and a lithium salt; The second filler is filled in the skeleton pores and forms a three-layer structure of first filler-second filler-first filler with the first filler.

4. The negative electrode sheet according to claim 3, characterized in that: The components of the second filler, measured by mass percentage, include: Polymer solid electrolyte 90%~99%; Lithium salt 1-10%.

5. The negative electrode sheet according to claim 3, characterized in that: The polymer solid electrolyte is at least one selected from polyethylene oxide, polyacrylonitrile and polymethyl methacrylate.

6. The negative electrode sheet according to claim 3, characterized in that: In the three-layer structure, the total height or volume of the skeleton pores is set to 1, the filling amount height or volume of the first layer accounts for 1 / 3 to 1 / 4, the filling amount height or volume of the second layer accounts for 1 / 3 to 1 / 2, and the filling amount height or volume of the third layer accounts for 1 / 3 to 1 / 4.

7. The negative electrode sheet according to claim 6, characterized in that: In the three-layer structure, the total height or volume of the skeleton pores is set to 1, the height or volume fraction occupied by the first layer is 1 / 3, the height or volume fraction occupied by the second layer is 1 / 3, and the height or volume fraction occupied by the third layer is 1 / 3.

8. The negative electrode sheet according to claim 1, characterized in that: The diameter of the skeleton pores is 1 to 100 mm.

9. The negative electrode sheet according to claim 1, characterized in that: The spacing between the skeleton holes is 1 to 100 mm.

10. The negative electrode sheet according to claim 1, characterized in that: When the depth of the skeleton pores is set to H, the distance between the skeleton pores is set to L, and the thickness of the negative electrode sheet is set to T, the following formula H≤T, L / T≥10 is satisfied.

11. The negative electrode sheet according to claim 1, characterized in that: The skeleton holes are evenly distributed at preset intervals in the horizontal and vertical directions.

12. The negative electrode sheet according to claim 2, characterized in that: The solid electrolyte is at least one selected from lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide lithium phosphorus sulfur, lithium phosphorus sulfur chlorine, and lithium germanium phosphorus sulfur.

13. The negative electrode sheet according to claim 1, characterized in that: The pole piece skeleton layer comprises a graphite layer and a copper foil layer, and the skeleton holes are arranged on the graphite layer.

14. The negative electrode sheet according to claim 1, characterized in that: The total volume of the skeleton pores occupies 10%-90% of the total volume of the pole piece skeleton layer.

15. The negative electrode sheet according to claim 1, characterized in that: The pole piece skeleton layer comprises one of graphite, hard carbon and soft carbon.

16. A method for preparing a negative electrode sheet, characterized in that: include: Mixing graphite, a conductive agent, sodium carboxymethyl cellulose glue, a binder and a solid electrolyte to obtain a first slurry; Applying the first slurry to a carrier to form a coating, and drying and rolling to obtain a current collector; Punching the current collector to obtain a pole piece skeleton layer; Filling the pores of the pole piece skeleton layer with filler slurry and drying the slurry to obtain a negative pole piece, wherein the filler comprises at least silicon-carbon material, conductive agent, sodium carboxymethyl cellulose glue and binder.

17. The method for preparing a negative electrode sheet according to claim 16, characterized in that: The filler includes a first filler and a second filler, and the step of filling the filler slurry into the pores of the pole piece skeleton layer and drying to obtain the negative pole piece includes: Filling the skeleton pores with the second slurry corresponding to the first filler, and controlling the filling height or volume to be 1 / 4 to 1 / 3 of the total height or volume of the skeleton pores, and then drying; The third slurry corresponding to the second filler continues to fill the skeleton pores, and the filling height or volume is controlled to be 1 / 3 to 1 / 2 of the total height or volume of the skeleton pores, and then dried; The second slurry corresponding to the first filler continues to fill the skeleton pores, and the filling height or volume is controlled to be 1 / 4 to 1 / 3 of the total height or volume of the skeleton pores, and then dried to obtain the negative electrode sheet.

18. A solid-state battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet described in any one of claims 1 to 15, or a negative electrode sheet prepared by the method for preparing the negative electrode sheet described in any one of claims 16 to 17.

Citation Information

Cited By

  • All-solid-state battery negative electrode material as well as preparation method and application thereof

    CN121172088A

  • Negative plate and silicon carbon battery

    CN121237808A